2020
DOI: 10.3390/biology9030047
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Model of Cancer Drug Resistance: Oncosomal Release of Cytotoxic and Antibody-Based Drugs

Abstract: Extracellular vesicles (EVs), such as exosomes or oncosomes, often carry oncogenic molecules derived from tumor cells. In addition, accumulating evidence indicates that tumor cells can eject anti-cancer drugs such as chemotherapeutics and targeted drugs within EVs, a novel mechanism of drug resistance. The EV-releasing drug resistance phenotype is often coupled with cellular dedifferentiation and transformation in cells undergoing epithelial-mesenchymal transition (EMT), and the adoption of a cancer stem cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 196 publications
(238 reference statements)
1
30
0
Order By: Relevance
“…CDC37 could positively regulate EMT and the release of EVs through permitting the function of these protein kinases. Consistently, recent studies have shown that EMT in cancer cells was often coupled with the release of EVs and drug resistance [22,98,99].…”
Section: Discussionsupporting
confidence: 60%
“…CDC37 could positively regulate EMT and the release of EVs through permitting the function of these protein kinases. Consistently, recent studies have shown that EMT in cancer cells was often coupled with the release of EVs and drug resistance [22,98,99].…”
Section: Discussionsupporting
confidence: 60%
“…Exosome-mediated enhanced EMT and stemness in the drug resistance of BC Recent studies have shown that the release characteristics of EVs are usually coupled with cellular phenotypic transformation, including EMT 81,82 and CSC 83,84 . EMT and stemness promote the EV-releasing phenotype of cells, and tumor-derived EVs could in turn initiate EMT and stemness in tumor cells 85 . Thus it is conceivable that the EMT and CSC phenotypes are involved in promoting tumor progression and the acquisition of therapeutic resistance mediated by exosomes.…”
Section: Exosomes Regulate Emt Cancer Stem Cell (Csc) and Tme In Thmentioning
confidence: 99%
“…Epithelial-mesenchymal transition (EMT) is a key biological event potentially regulated by extracellular HSP90 [19,20]. EMT involves phenotypic changes in cells from epithelial to mesenchymal properties and promotes motility [21], migration, invasion, stemness [22], and drug resistance [23][24][25] in various types of cancer cells [26]. Numerous EMT-promoting factors have been identified, although recent studies, including ours, have revealed that cancer cell-derived EVs often initiate EMT in epithelial cells [8,10] and promote EMT in tumour cells [27].…”
Section: Introductionmentioning
confidence: 99%